2019
DOI: 10.3390/nu11122845
|View full text |Cite
|
Sign up to set email alerts
|

Served Portion Sizes Affect Later Food Intake Through Social Consumption Norms

Abstract: Portion sizes of commercially available foods have increased, and there is evidence that exposure to portion sizes recalibrates what is perceived as ‘normal’ and subsequently, how much food is selected and consumed. The present study aims to explore the role of social (descriptive and injunctive) and personal portion size norms in this effect. Across two experiments, participants were either visually exposed to (Study 1, N = 329) or actually served (Study 2, N = 132) a smaller or larger than normal food portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…People eat more when they are given multiple small packages, however, a phenomenon referred to as the partitioning paradox [82]. Several studies outside this review have suggested that the impact of cues such as package and portion size can (partially) be explained by normative influence, whereby people rely on these cues to make judgements about the appropriate consumption size [83,84]. However, no study in the review measured whether perceived norms function as a mediator of the package size effect.…”
Section: Discussionmentioning
confidence: 92%
“…People eat more when they are given multiple small packages, however, a phenomenon referred to as the partitioning paradox [82]. Several studies outside this review have suggested that the impact of cues such as package and portion size can (partially) be explained by normative influence, whereby people rely on these cues to make judgements about the appropriate consumption size [83,84]. However, no study in the review measured whether perceived norms function as a mediator of the package size effect.…”
Section: Discussionmentioning
confidence: 92%
“…As far as we are aware, this is the first study to empirically examine different psychological responses towards an increased proportion of plant-based foods available in assortment structures [7,8]. We particularly showed that descriptive norms can be inferred from the number of plant-based foods available, providing further evidence for the proposition that social norms are embedded in physical aspects of food environments [17,19,25]. The proportion of plant-based (versus animal source) foods available may serve as a cue that implies a consumption norm reflecting what other people typically choose, rather than reflecting the appropriate choice according to others (i.e., an injunctive norm).…”
Section: Discussionmentioning
confidence: 53%
“…Consumers observing a relatively greater supply of plant-based foods may believe that these products are popular because of a high demand (i.e., greater consumption of these products by others) [7]. This explanation is related to a descriptive norm indicating what other people normally do in that environment [18]; it is supported by previous studies suggesting that descriptive norms can influence behavior through physical aspects in food environments without seeing others [17,[19][20][21]. Likewise, we argue that consumers may (also) infer that a greater availability of plant-based foods signals what other people consider as the appropriate choice in that environment.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations